The origins of “Kaunayen” game fowls of Manipur, India: Insights from mitochondrial D-loop sequence analysis - Robin Singh Mutum; Abhik Das; Sankar Kumar Ghosh; Vidyarani Devi Wangkheimayum (Poultry Science)
Notably, poultry animals—particularly chickens—are recognized globally for their valuable contributions to the food, ornamental, and game economies. Further, more robust local and regional breeds can be parental donors for these area-specific consumable breeds' resilient traits. Game birds that are locally significant economically or on a much smaller scale are frequently excluded from the procedure. One such breed is the fighting chicken of Manipur, India, known locally as the Kaunayen breed and listed as the 17th breed at the ICAR, the National Bureau of Animal Genetic Resources, India. When Kaunayen fowl from throughout Manipur are considered, they have anatomical characteristics and common behavioural traits despite the breed's extreme genetic heterogeneity. With this gap in mind, we attempted to use mitochondrial D-loop sequences to characterize Manipur's Kaunayen fowls concerning the global breeds of nearly similar molecular characteristics. We found that Kaunayen fowls share evolutionary traits such as a similar transition/transversion ratio with some Southeast Asian breeds, including a few red jungle fowls. Overall Kaunayen are also more closely related to Southeast Asian birds phylogenetically, after which with a few breeds from East Asian, Bangladesh, North-East India, and the Indian island of Nicobar. The global database including our query has 19 haplotypes, and majority of the Kaunayen fowls share haplotypes with North East Indian fowls; the remaining haplotypes are primarily associated with South East Asia and East Asia. The findings additionally indicated that Kaunayen's and the global breed's D-loop region tended to fixed neutral substitution, contributing to the distinct varieties. Further, migration research demonstrated that Kaunayen fowls originated from a substantial maternal genome influx from Southeast Asia, which may have later made a substantial contribution to East Asian and South Asian breeds.We also display a portion of the D-loop that demonstrates the majority of the substitution diversity across all breeds, and we suggest using sequence stretch to create miniature breed-specific identifying barcodes.